ANALISIS KEPUASAN DAN LOYALITAS KONSUMEN TERHADAP PISANG RAJA SEREH DAN PISANG CAVENDISH DI KOTA BANDAR LAMPUNG - M Hutama Pandu Negara AT; Suriaty Situmorang; Dame Trully Gultom (Lampung University, 2020)
The aims of this research are to determine the satisfaction, and loyalty of consumers to Raja Sereh Bananaand Cavendish Banana products in Bandar Lampung City. The research is conducted in June to July 2018.The samples are consumers of Raja Sereh Banana and Cavendish Banana that are recruited byaccidentalsampling. The number of consumer respondents are 80 people, divided by 40 respondent of Raja SerehBanana and 40 respondent of Cavendish Banana. This research is conducted in two different locations,namely traditional market (Pasir Gintung Market) and modern market (Gelael Supermarket). The researchdata is analyzed by descriptive analysis, namely Consumer Satisfaction Index Analysis (CSI) and LoyaltyPyramid. The results of this research showed that Raja Sereh Banana and Cavendish Banana consumerswere “satisfied” and “loyal”. Consumer satisfaction of Raja Sereh Banana was 74.66 percent and theconsumer satisfaction of Cavendish Banana consumer was 71.09 percent. The level of consumer loyalty wasclassified as a buyer who was committed with a value of 85.00 percent for Raja Sereh Banana and 90.00percent for Cavendish Banana.Key words:bananas, consumer, loyalty, satisfaction